UPAYA MENINGKATKAN HASIL BELAJAR KETERAMPILAN GERAK DASAR ANAK MELALUI PENDEKATAN BERMAIN - Jumat, Yosef Jawa (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The background of this research is that the implementation of Physical Education, Sports and Health learning at SD Inpres Waiwadan, especially in the Long Jump material, is still far from expectations, this is evidenced by the results of students' long jump learning at this time who still do not meet the KKM. This study aims to describe the process of improving long jump learning outcomes through the jumping rope approach to fourth grade students of SD Inpres Waiwadan, West Adonara Subdistrict, East Flores Regency in 2018/2019. This research is a classroom action research. The subjects in this study were fourth grade students of SD Inpres Waiwadan, West Adonara District, East Flores Regency with a total of 20 people consisting of 11 male students and 9 female students. The instrument used was the long jump performance test. The data analysis technique used in this research is descriptive qualitative and quantitative. Based on the results of the study, it can be concluded that the increase in long jump results through playing rope jumping in the fourth grade students of SD Inpres Waiwadan, West Adonara District, East Flores Regency in 2018/2019 was marked by an increase in the average score of students' daily tests. The average score of students' daily tests in pre-action activities was 72.65 with a completeness percentage of 65%. This condition experienced an increase in the average score of students' daily tests in the first cycle, which was 79.45 and the percentage of completeness was 85%. However, this increase has not yet reached the target previously set. Then after continuing to cycle II the average score of the students' daily long jump tests again increased by 81.45 with a completeness percentage of 90%. This shows that the targets that have been previously set have been achieved so that the research was stopped in cycle II. The long jump learning process using the jumping rope approach is dynamic and fun. Students actively carry out tasks and observe long jump technique movements and discuss mutual discussions with friends. All aspects of the assessment are controlled by students. The long jump ability of students increases marked by all students completing the KKM (Minimum Completion Criteria), namely 75. Â 